If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 4 = 38 Reorder the terms: 4 + 2y = 38 Solving 4 + 2y = 38 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2y = 38 + -4 Combine like terms: 4 + -4 = 0 0 + 2y = 38 + -4 2y = 38 + -4 Combine like terms: 38 + -4 = 34 2y = 34 Divide each side by '2'. y = 17 Simplifying y = 17
| g=2+6t | | n^6=6 | | 5-2y=1.5 | | 9x-6=3x-30 | | 7a+4=5a+8 | | 7(b-5)+12=5 | | 16Y=15(y+13) | | 4f-2=18 | | -107=3+10x | | 0.04(12)+0.01x=0.02(12+x) | | 2x-18=5x+12 | | -7(3x+9)=-21x+63 | | n+21=24 | | 4x+b=3x+7 | | 5(5x-20)=25(x-20) | | 8y-8=37-7t | | 9x^2-18x+5= | | y-6=x | | 8850=x^2-14x+63 | | 4y-9+y+20=5y+20-3y | | .5x=-1.5x+4 | | 20+(-7)= | | m/20+100=460 | | 5-2y=-1.5 | | -22+-35= | | -7-8x=-9x+14 | | 2x-3a+4x+2a-5x=0 | | m/20-100=460 | | m/100-20=460 | | m/100+20=460 | | 16(3x-2)=4(12x+5) | | 6g+2(-6+2g)=1-g |